Pengaruh Pengetahuan Tour Guide dan Keterampilan Tour Guide Terhadap Kepuasan Wisatawan di Kota Tua Jakarta, Indonesia - Pusparani, Pusparani; Boediman, Surya Fadjar; Nasution, Deivy Zulyanti; Rachman, Arief Faizal; Hutagalung, Husen (Jurnal Ilmiah Pariwisata, 2024)
The Old City of Jakarta, as a historical tourist destination, requires competent tour guides to increase tourist satisfaction. This research aims to analyze the influence of tour guide knowledge and skills on tourist satisfaction. The method used was quantitative research with a cross-sectional design, involving 150 randomly selected respondents. Data was collected through questionnaires and analyzed using validity, reliability and multiple linear regression tests. The research results show that tour guide knowledge has a positive and significant influence on tourist satisfaction with a p value <0.05. Apart from that, communication skills also make a significant contribution in increasing tourist satisfaction. The discussion shows that tour guides who have a deep understanding of the tourist attraction and good interpersonal skills can create a more satisfying tourism experience. The conclusion of this research emphasizes the importance of increasing the competence of tour guides in order to increase tourist satisfaction. The advice for tour guides is to continue to develop their knowledge and skills, while tourists are expected to interact more actively with guides. Further research is recommended to explore other variables that can influence tourist satisfaction in various locations. Keywords: knowledge, skills, tourist satisfaction, tour guides